At the nexus of work and togetherness: Family agriculture in Madura, Indonesia - Kristina, Anita; Jumali, Muhamad Abdul; Kamsin, Khairunisah Binti (Center for Sociological Studies and Community Developmen, 2025)
This study aims to explore how families understand and organize their work in agriculture in the midst of modern production challenges and changing agricultural practices, specifically in Madura, Indonesia. This research uses a qualitative research methodology with a phenomenological approach. This study analyzes the responses of informants to understand the lived experiences of farming families. Using the theory of symbolic interactionism, this research shows how farmers negotiate their work and family roles through the active construction and prioritization of shared meanings related to togetherness. These principles include a) a simple way of thinking, b) owning a traditional small farm, and c) not being primarily market oriented. Farmers foster a sense of work-related togetherness by forming strong family ties, resulting in a division of labor and wages based on family relationships. In the Madurese context, traditional agricultural practices are not only a means of livelihood, but also an integral part of the family's cultural identity and social structure. The findings of this study underscore the crucial role of shared meanings related to togetherness and family solidarity in sustaining traditional agriculture in the modern era. It also provides insights into the importance of family cohesion as a fundamental element of the resilience of traditional agricultural practices in Madura, Indonesia.